2006
DOI: 10.1007/s11270-005-9050-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Mapping Critical Loads of Acidity and Exceedances for Upland Forest Soils in Eastern Canada

Abstract: Critical loads of acidity were estimated for upland forests in Eastern Canada using the steady-state Simple Mass Balance (SMB) Model. A consistent methodology was applied to the entire region, although critical loads were estimated separately for the Atlantic provinces (New Brunswick, Nova Scotia, Prince Edward Island and Newfoundland), Quebec and Ontario using different data sources. In this project, critical load estimates and steady-state exceedance values did not include the effect of forest fire and fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 12 publications
1
50
0
Order By: Relevance
“…The coarser grain size fractions (sands) probably do not differ much in bulk chemistry and mineralogy relative to the finer particles (silt and clay) but differences in specific surface area and reactivity to acidic solutions may be large (Stillings and Brantley, 1995). The sum of the modeled BC + Na weathering average values (1.71 kmol c ha −1 yr −1 ) and the average net catchment exportation values (1.20 kmol c ha −1 yr −1 ) are two to three times higher than previous WRs reported by Ouimet et al (2006) for the soils of a vast area of the province of Québec (typically lower than 0.5 kmol c ha −1 yr −1 ). In this latter study, a relationship using soil texture was used to generate soil WRs.…”
Section: Modeled Weathering Ratesmentioning
confidence: 68%
See 1 more Smart Citation
“…The coarser grain size fractions (sands) probably do not differ much in bulk chemistry and mineralogy relative to the finer particles (silt and clay) but differences in specific surface area and reactivity to acidic solutions may be large (Stillings and Brantley, 1995). The sum of the modeled BC + Na weathering average values (1.71 kmol c ha −1 yr −1 ) and the average net catchment exportation values (1.20 kmol c ha −1 yr −1 ) are two to three times higher than previous WRs reported by Ouimet et al (2006) for the soils of a vast area of the province of Québec (typically lower than 0.5 kmol c ha −1 yr −1 ). In this latter study, a relationship using soil texture was used to generate soil WRs.…”
Section: Modeled Weathering Ratesmentioning
confidence: 68%
“…In this latter study, a relationship using soil texture was used to generate soil WRs. It strongly suggests that this relationship was not totally adequate at least for Quebec soils and as a result, Ouimet et al (2006) probably underestimated WRs. Koseva et al (2010) recently reported that WRs estimated with PRO-FILE were seven times higher than WRs estimated from a relationship with soil texture, in good agreement with our results.…”
Section: Modeled Weathering Ratesmentioning
confidence: 99%
“…Critical loads have a central role in pollution management and are used for mapping pollution impacts, controlling and permitting individual pollution sources, and framing international negotiations on transboundary air pollution. They have recently been applied in the United States (3) and Canada (4), and they are under active consideration and development in many parts of the developing world (5).…”
mentioning
confidence: 99%
“…in part of its range has been concomitant with a decrease in base cation availability on many sites (Bailey et al 2004;Fenn et al 2006;Watmough et al 2005). In two regional studies on the effect of atmospheric acid deposition on forest ecosystems, a majority of sites in the hardwood forest of eastern Canada and New England states were found to exceed their critical acid load (McNulty et al 2007;Ouimet et al 2006). This suggests that the supply of Ca, the most abundant of the base cations, is generally decreasing in most of the hardwood forest range.…”
Section: Many Forests Of Southern Quebec and Eastern Ontario As Wellmentioning
confidence: 99%